Tentsmuir : ten thousand years of environmental history - Crawford, R. M. M. (Archaeopress Publishing Ltd, 2019)
Tentsmuir, North East Fife, has seen human activity for over 10,000 years. The area provides a natural refuge for a wide range of plants, resident and migrating birds, and an array of animal and insect life. This text investigates how plant and animal communities are constantly reacting to the environmental changes common to the region.